До історії створення першого повного зібрання творів Лесі Українки (1923-1925рр.) - Радько, Антоніна; Rad’ko, Antonina (Східноєвропейський національний університет імені Лесі Українки, 2015)
Йдеться про історію першого багатотомного видання творів Лесі Українки 1923–1925 рр.: організацію роботи, укладання, композиційну будову томів тощо. На підставі родинного листування Косачів та інших матеріалів, використаних у статті, вирізнено роль К. Квітки, Б. Якубського і М. Зерова.The article deals with the history of the first multivolume publication of Lesya Ukrainka’s works during 1923−1925: organization of work, styling, composite structure of volumes and so on. Activity of publishing house “Knyhospilka” during this period is presented as well as activities of editors and commentators: K. Kvitka, M. Zerov, B. Yakubskuy, P. Fylypovych, J. Mamontov and G. Holoskevych. The role of K. Kvitka, B. Yakubskuy and M. Zerov is pointed out based on the family correspondence the Kosach and other materials used in the article. The methods and techniques for working with text editors are paid attention to, original printings are marked among the published works. The importance of the release of this collection of essays is emphasized because it gave a great and significant material for further study of Lesya Ukrainka’s creative heritage, formed textual principles of personal and laid the foundation for subsequent editions of her works.
From the History of Creation of Lesya Ukrainka’s First Complete Works (1923–1925)
Keywords: зібрання творів; текст; том; видання; видавництво; текстологія; collected works; text; volume; edition; publishing house; textology